Synthesis report on codes of conduct, voluntary measures and practices towards a responsible development of nanoparticle and nanotechnology (Roma, 2010)
"This report, from the European NanoCode Project, details what governments worldwide and other stakeholders to ensure the responsible development of nanotechnologies, including regulation, the sharing of information, and the development of best practices. The report discusses the national strategies and level of activity in different countries as regards social and environmental health and safety issues related to nanotechnology development, as well as voluntary initiatives that relate to the development of the European Communities Nanotechnology Code of Conduct for Nanosciences and Nanotechnologies."